HUBUNGAN TINGKAT PENDIDIKAN DENGAN KEPATUHAN PERAWAT PELAKSANAAN STANDAR PROSEDUR OPERASIONAL PENERIMAAN PASIEN BARU DI RUMAH SAKIT HATIVE PASSO - Bazrul Makatita; Yunita Rahanwatty (Pasapua Health Journal, 2022)
Introduction: one form of health service in a hospital is the Emergency Room (ER). Fast and precise service is needed in emergency room services. However, services in the ER can be hampered if the conditions in the ER are full of patients. Conditions like this can cause nurses to ignore the importance of implementing Standard Operating Procedures. Purpose: to determine the relationship between education level and nurse compliance with standard operating procedures for admitting new patients at Hastive Passo Hospital. Method: this study used a descriptive survey design and used the Chi Square test. The population in this study were all nurses working daily at the emergency room at Hative Passo Hospital. The sampling technique used is total sampling. The sample in this study were 36 respondents. Results: Research from 36 respondents at Hative Passo Hospital showed that the majority of respondents had a level of compliance, 26 respondents (72.2%) who obeyed, and 10 respondents (27.8%) who did not comply, with p = 0.524. Conclusion: Based on the data analysis used the chi square test, it can be said that there is no relationship between the education level of nurses and compliance with the implementation of standard operating procedures for admitting new patients at Hative Passo Hospital